2014
DOI: 10.1111/bju.12789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a genomic classifier test on clinical practice decisions for patients with high‐risk prostate cancer after surgery

Abstract: ObjectivesTo evaluate the impact of a genomic classifier (GC) test for predicting metastasis risk after radical prostatectomy (RP) on urologists' decision-making about adjuvant treatment of patients with high-risk prostate cancer.Subjects and MethodsPatient case history was extracted from the medical records of each of the 145 patients with pT3 disease or positive surgical margins (PSMs) after RP treated by six high-volume urologists, from five community practices. GC results were available for 122 (84%) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 25 publications
3
21
0
1
Order By: Relevance
“…This indicates that implementation of the GC test in clinical practice carries the potential to improve allocation of healthcare resources by ensuring that adjuvant therapy is targeted for use by those patients who are truly at higher risk of disease progression. These results are consistent with the ASSESS-D study, which showed that the GC test may result in reductions in treatment intensity after surgery for the majority of patients tested 15 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This indicates that implementation of the GC test in clinical practice carries the potential to improve allocation of healthcare resources by ensuring that adjuvant therapy is targeted for use by those patients who are truly at higher risk of disease progression. These results are consistent with the ASSESS-D study, which showed that the GC test may result in reductions in treatment intensity after surgery for the majority of patients tested 15 .…”
Section: Discussionsupporting
confidence: 90%
“…The ASSESS-D study found, among patients classified as low risk by the GC test (72%), observation was recommended 81% of the time, on the basis of reviewing both GC test results and clinical variables. Treatment was planned 65% of the time for patients with GC test results, indicating increased risk of progression; also test results were highly correlated with the chosen treatment intensity (e.g., observation to treatment including multimodal therapy) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study suggest that Decipher can be used as a standard tool to better risk-stratify patients based on clinical and pathologic risk factors. Recent studies show that Decipher influences physician postoperative decision making in the adjuvant setting and lowers the discrepancy in decision making between urologists and radiation oncologists [38][39][40].…”
Section: [ ( F I G _ 3 ) T D $ F I G ]mentioning
confidence: 99%
“…Тем не менее некоторые генетические подписи, аппробированные на большом клиническом материале, показали многообещающие результаты при оценке в послеоперационном периоде у больных РПЖ высокого риска, но эти результаты нуждаются в дальнейшей оценке в масштабных проспективных исследованиях [23]. Однако на этапе биопсии ткани (первый минимально-инвазивный контакт с опухолью) проблема ее генети-ческой характеристики на сегодняшний день не решена.…”
Section: о н к о у р о л о г и я 100unclassified